KONSEP KOSMOLOGI HINDU DALAM TEKS TUTUR BHUWANA MAREKA - Ida Bagus Putu Adnyana; I Wayan Redi; I Gusti Made Widya Sena (Pangkaja: Jurnal Agama Hindu, 2021)
The lack of research and in-depth discussion of the concept of Hindu Cosmology became the basis for researchers to conduct this research. This study uses the text of Tutur Bhuwana as the object of research. The purpose of this study is to be able to analyze the concept of Hindu Cosmology (Virat Vidyā) in the Tutur Bhuwana Mareka text, especially in the aspects of creation (uttpti), maintenance (stiti), and annihilation (pralina) of the universe. This research is a type of research that uses qualitative methods by conducting research or literature studies and searching online data as a data collection technique. The use of this method is to obtain in-depth information related to the concept of Hindu Cosmology (Virat Vidyā) in the Tutur Bhuwana Mareka text. Mainly related to the process of creation, maintenance, and dissolution of the universe. The process of creation (uttpti) of the universe in the text of Tutur Bhuwana Mareka begins in a very quiet and empty state of the universe (hning sunya nirbhana). Then came Sang Hyang Nora as the initial entity for the emergence of Sang Hyang Mareka Jati as the beginning of the process of creating the universe. Then there is the maintenance process (stiti) of the universe which is based on the basic concept of the Tri Sakti which includes the mind (idep), breath (bayu) and sound (sabda). And the last is the process of fusion (pralina) of the universe which adheres to the concept of Shiva Linga. This concept describes the process of creating the universe by Sang Hyang Mareka Jati, who will eventually return to Him as the highest entity.